2000
DOI: 10.1002/1097-4636(20001215)52:4<577::aid-jbm1>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Really smart bioconjugates of smart polymers and receptor proteins

Abstract: Over the past 18 years we have been deeply involved with the synthesis and applications of stimuliresponsive polymer systems, especially polymerbiomolecule conjugates. This article summarizes our work with one of these conjugate systems, specifically polymerprotein conjugates. We include conjugates prepared by random polymer conjugation to lysine amino groups, and also those prepared by site-specific conjugation of the polymer to specific amino acid sites that are genetically engineered into the known amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…However, improvements are required in many areas, such as prevention of non-specific binding [302][303][304][305][306], sensitivity [307][308][309][310][311][312][313][314][315], site-specific conjugation [316][317][318], bioactivity [319][320][321][322], multiplexing [309,323], and reusability [324][325][326]. Some of these problems can be addressed by using different chemical surface modification approaches.…”
Section: Biosensing-detectionmentioning
confidence: 99%
“…However, improvements are required in many areas, such as prevention of non-specific binding [302][303][304][305][306], sensitivity [307][308][309][310][311][312][313][314][315], site-specific conjugation [316][317][318], bioactivity [319][320][321][322], multiplexing [309,323], and reusability [324][325][326]. Some of these problems can be addressed by using different chemical surface modification approaches.…”
Section: Biosensing-detectionmentioning
confidence: 99%
“…50 In many cases, the change in the state of the polymer is reversible. Smart synthetic polymers may revolutionize improvements in tissue engineering scaffolds.…”
Section: 폴리머 제38권 제2호 2014년mentioning
confidence: 99%
“…Hoffman and Stayton, leaders in the field of responsive polymer protein conjugates, have various publications that have applications as "molecular switches" and for enzyme recovery (34,54,(107)(108)(109)(110)(111). They have demonstrated that a polymer chain attached at a specific conjugation site can act as a "molecular switch" controlling enzyme activity through thermal or photoactive control (Figure 8).…”
Section: Stimuli-responsive Conjugates Stimuli-responsive Polymers (mentioning
confidence: 99%